Disabling the Steering Wheel? National and International Actors' Climate Change Mitigation Strategies in Latin America - Miguel Rodriguez Lopez; Daniele Vieira do Nascimento; Daniela Garcia Sanchez; Martha Bolivar Lobato (German Institute of Global and Area Studies (GIGA), 2015)
This article addresses the question of how Brazil, Costa Rica, and Colombia came to decide on their climate change mitigation strategies, which are based on market-oriented policies. The analysis compares Brazilian bioethanol, Costa Rican renewable energy, and Colombia's clean development mechanism. Using the 'chicken game,' the best response is to 'disable the steering wheel.' This means that an actor reduces his or her capacity for action in order to signal a commitment to continue acting in line with his or her past behaviour. The study assesses this strategy at the level of relationships between national and international actors. The findings show that the national actors examined here are either continuing with criticised projects, in the Brazilian case, or slowing down their mitigating strategies, in the cases of Costa Rica and Colombia, and thereby restricting their capacity for action in order to reach a better negotiating position.
Keywords: 300; climate change; mitigation; bioethanol; energy; carbon markets; Brazil; Costa Rica; Colombia